silver n / silver thaw (1987)
silver thaw n Although the sun was brilliant there was a lot of silver thaw around. PRINTED ITEM DNE Sup [Add as post 1960/1970 cite] GMS WK Sep 87 Used I and Sup Used I and Sup Not used GLITTER, SILVER FROST Source not used in DNE